Squamous Cell Carcinoma as a Complication of Long-Term Hydroxyurea Treatment - Miłosz Lewandowski; Paweł Łukowicz; Jerzy Jankau; Jan Romantowski; Wioletta Barańska-Rybak (Karger Publishers, 2021)
Hydroxyurea therapy is commonly used in the treatment of patients suffering from myeloproliferative diseases, such as polycythemia vera. It is supported by evidence that this type of therapy can generate mild skin lesions like leg ulcers, erythema, and hyperpigmentation. There are also some studies that show an increased risk of development of nonmelanoma skin cancers. We report a 56-year-old man with a 13-year history of polycythemia vera, treated chronically with hydroxyurea. In April 2020, the patient presented a skin lesion on the forehead, skin horn on the left forearm, and hyperkeratosis on the rims of both ears. In the patient's history, in October 2019, complete excision of the skin lesion in the central area of the forehead was performed. After 4 months, a new skin lesion appeared at the same area of the forehead, which in May 2020 after resection in the histopathological examination was diagnosed as recurrence of squamous cell carcinoma. The aim of the case is to draw the clinicians' attention to the increased risk of squamous cell carcinoma and basal cell carcinoma in patients treated with hydroxyurea. Increased vigilance would make it possible to recognize them earlier, and thus potentially reduce the undesirable effects associated with the delayed radical treatment of these skin cancers. Randomized clinical trials assessing the potential benefits of oral retinoids for chemoprevention of nonmelanoma skin cancers in the hydroxyurea-treated population should also be considered.